Wound Healing After Wet Cupping Therapy (Descriptive) at Fort De Kock University, Bukittinggi - Putri, Lydia Mardison; Wati, Del Fatma (Universitas Fort De Kock Bukittinggi, 2025)
Cupping is one part of Complementary And Alternative Therapy (CAT) therapy . The benefits of cupping therapy are claimed to maintain health by removing toxins from the body, but scars are at risk of infection if not done properly . The purpose of this study was to determine the picture of cupping wound healing after 3 days of treatment. This study is quantitative with a descriptive research design . The population in this study were cupping patients aged 18-26 years, with a sample size of 200 people, sampling by purposive sampling , this study used a research instrument for measuring secondary wound healing issued by the Nursing Outcomes Classification (NOC), data were analyzed univariately. The results of the univariate analysis showed that all 100% of patients who underwent cupping therapy had a good wound healing process, none of whom were found to have wound infections after 3 days after wet cupping. It is expected that every nurse who performs cupping therapy will continue to pay attention to standard operating procedures (SOP), sterile principles and disinfectant areas of the injection.